2017
DOI: 10.1080/09645292.2017.1315055
|View full text |Cite
|
Sign up to set email alerts
|

The more, the better? The impact of instructional time on student performance

Abstract: Although instruction time is an important and costly resource in education production, there is a remarkable scarcity of research examining the effectiveness of its use. We build on the work of Lavy (2015) using the variance of subject-specific instruction time within Switzerland to determine the causal impact of instruction time on student test scores, as measured by the international PISA test (2009). We extend the analyses in two ways and find that students must differ considerably in the time needed to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
(21 reference statements)
1
53
1
4
Order By: Relevance
“…Indeed, others in the economics of education field have used similar methods (e.g. , Hanushek, Piopiunik, and Wiederhold 2014, and Cattaneo, Oggenfuss and Wolter 2017. Although the substantive conclusions these papers reach may or may not be undermined, we nevertheless argue that the special features of the PISA data mean that the common econometric identification strategies used in these papers should have been through a series of important additional robustness tests (which we shall describe in section 5 of this paper).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, others in the economics of education field have used similar methods (e.g. , Hanushek, Piopiunik, and Wiederhold 2014, and Cattaneo, Oggenfuss and Wolter 2017. Although the substantive conclusions these papers reach may or may not be undermined, we nevertheless argue that the special features of the PISA data mean that the common econometric identification strategies used in these papers should have been through a series of important additional robustness tests (which we shall describe in section 5 of this paper).…”
Section: Introductionmentioning
confidence: 99%
“…"… due to inadequate preparation for lessons" (T3) "… laziness". (T12) Time is an important variable and costly resource in education production (see Carrol, 1963;Cattaneo, Oggenfuss and Wolter, 2017;Vannest and Hagan-Burke, 2010), therefore it must be used effectively and judiciously.…”
Section: Inadequate Preparation Lateness and Lazinessmentioning
confidence: 99%
“…Despite the significance of the usage of allocated instructional time and engaged instructional time for effective teaching and learning as well as harnessing the potentials of the nation's resources (see Cattaneo, Oggenfuss and Wolter, 2017;Carroll, 1989;Fisher & Berliner, 1985;Walberg, 1988) very little accessible discussion of this exists in the context of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Raising instructional time -the allocated number of hours per year that students spend in formal classroom settings -is often found to have positive effects on cognitive skills such as maths and language ability (Bellei, 2009;Cortes and Goodman, 2014;Taylor, 2014), as well as standardised maths, reading, and scientific literacy test scores (Andrietti, 2016;Cattaneo et al, 2016;Huebener et al, 2017). 1 Differences in instructional time between countries are also found to account for some of the observed international gaps in student achievement (Lavy, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…This type of behaviour can cover a broad range of actions such as helping, sharing, and other forms of cooperation (Batson and Powell, 2003), and is distinct from altruism in that it is not purely motivated by increasing another individual's welfare, but can be motivated by, for example, empathy, reciprocity, or self-image (Evren and Minardi, 2017). Pro-social behaviour, and in particular volunteering, is linked to various positive outcomes: at the societal level, it can help build social capital through fostering cooperation and trust and through promoting citizenship (Putnam, 2000), and social capital is linked to higher levels of subjective well-being in societies (Helliwell et al, 2011); at the individual level, it is found to nurture important cognitive and non-cognitive skills that can improve individual 1 There is growing evidence that the effect of raising instructional time on student learning and performance is heterogeneous, and in particular, that higher-performing students tend to benefit relatively more (Cattaneo et al, 2016;Huebener et al, 2017). 2 The importance of instructional time for student achievement varies between educational systems, and in particular, between developed and developing countries (Woessmann, 2016), pointing towards potentially important complementarities in educational production, for example, between instructional time and teacher quality or effective classroom management techniques (Rivkin and Schiman, 2015).…”
Section: Introductionmentioning
confidence: 99%